Potassium and phosphorus fertilization impacts on bermudagrass and limpograss herbage accumulation, nutritive value, and persistence - Silveira, Maria L.; Vendramini, Joao M. B.; da Silva, Hiran M. S.; Borges, Bernardo M. M. N. [UNESP]; Ribeirinho, Victor S.; Lacerda, Julian J. J.; Azenha, Mariana V.; Viegas, Pedro R. A.; Aguiar, Andre D. (Wiley, 2017)
Despite scientific evidence suggesting that warm-season grasses can respond favorably to K and P fertilization, the increasing costs of fertilizers limit the extent to which these nutrients are used in pastures and hayfields. Two field studies evaluated ‘Jiggs’ bermudagrass [Cynondon dactylon (L.) Pers.] and ‘Floralta’ limpograss (Hemarthria altissima Stapf. and Hubbard) herbage accumulation (HA), nutritive value, and persistence to reduced fertilization strategies during 2012 to 2014. Treatments were allocated in a split-plot design with N (90 or 180 kg N ha−1, bermudagrass study) or harvest frequency (6 vs. 12 wk, limpograss study) as the main factors and P (0, 8.7, and 17.4 kg P ha−1) and K (0, 33, and 66 kg K ha−1) levels as subplots. Bermudagrass HA increased linearly (up to 377% in Year 3) as K level increased. Similarly, K fertilization increased limpograss HA from 8.4 to 11.6 Mg ha−1 in 2013 and from 5.8 to 15.7 Mg ha−1 in 2014 as K levels increased from 0 to 66 kg K ha−1; however, no effect was observed in 2012. Bermudagrass HA and ground cover decreased from 2012 to 2014 in all K treatments. Conversely, decreases in limpograss HA and ground cover over time were observed only in the control (no K) treatments. Bermudagrass and limpograss crude protein concentrations generally decreased with increased K level. No effects of N or P were observed. Continuous aboveground removal without proper K fertilization is detrimental to bermudagrass and limpograss production and persistence.